The relationship between service quality and customer loyalty at MS Garden Hotel Kuantan, Pahang / Wan Adli Wan Ahmad - Wan Ahmad, Wan Adli (2014)
The main purpose of business is to serve their customer. Many researches had proven that service quality is what influencing most in the business daily routine and one of the crucial factors to retain the customers. Excellence in service quality is a key to achieve customer loyalty which is the primary goal of business organizations, due to the advantages of customer retention (Ehigie, 2006). This study reports the relationship between the service quality and customer loyalty at the MS Garden Hotel Kuantan, Pahang. Many organizations try to retain their customers and do their best to retain their customers loyalty towards their service provided. However, how deep does the service quality been penetrating the loyalty of their customers is still a questions. The data were gathered based on the surveys made towards the customers of MS Garden Hotel Kuantan which related to the service qualities provided and their loyalty.